Factors affecting code switching between Arabic and English - Hafez, Rana Medhat (AUC Knowledge Fountain, 2015)
Code switching in the Arab world has been discussed extensively. This study explores different factors that affect the process of code switching between English, Egyptian Colloquial Arabic, and Modern Standard Arabic among a specific cohort. It examines how speakers position themselves and reflect their identities by using different associations of different codes in formal and informal settings. Data were collected through observations, a demographic questionnaire and interviews from eight board members at the Leo Club of Alexandria, Egypt, a charity and community service club. Five general and board meetings were recorded and transcribed in order to investigate the occurrence of code switching during these meetings. The eight participants filled out the demographic questionnaire. Interviews with the participants were then conducted in an attempt to examine their perceptions about code switching and why they personally use a specific code in different situations. Results reveal that social class, education, and gender appear to be the most important factors affecting participants’ choice of codes. In addition, most of the participants were found to use code switching in order to position themselves in a powerful state that gives them confidence and authority.